2015
DOI: 10.1002/pros.23038
|View full text |Cite
|
Sign up to set email alerts
|

Index lesion characterization by 11C‐Choline PET/CT and Apparent Diffusion Coefficient parameters at 3 Tesla MRI in primary prostate carcinoma

Abstract: In spite of the fact that PET imaging has higher tumor sensitivity than MRI, (11) C-Choline PET and ADC maps have complementary roles in the evaluation of Index Lesion in PPC. Index PET and Index MRI could be complementary targets in the therapeutic planning of PPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Diffusion-weighted imaging (DWI) is a commonly used magnetic resonance imaging (MRI) method for the diagnosis of prostate cancer (4)(5)(6). It was reported that apparent diffusion coefficient (ADC) values derived from DWI are generally lower in prostate cancer than those of non-cancerous prostate tissues (7), particularly in the peripheral zone (4). Thus, DWI is regarded as an important biomarker in multiparametric MRI; in particular, in the peripheral zone, DWI has been accepted as a determinant method for the detection of prostate cancer (8).…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) is a commonly used magnetic resonance imaging (MRI) method for the diagnosis of prostate cancer (4)(5)(6). It was reported that apparent diffusion coefficient (ADC) values derived from DWI are generally lower in prostate cancer than those of non-cancerous prostate tissues (7), particularly in the peripheral zone (4). Thus, DWI is regarded as an important biomarker in multiparametric MRI; in particular, in the peripheral zone, DWI has been accepted as a determinant method for the detection of prostate cancer (8).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular imaging with PET is one of the most promising tools for the investigation of PCa (Scher et al, 2007 ; Hernández-Argüello et al, 2016 ). PET-guided prostate biopsy implementation could be not only plausible, but also mandatory in some subjects with contraindications to MRI or high clinical probability of prostate cancer, associated to negative MRI.…”
Section: Introductionmentioning
confidence: 99%
“…PET-guided prostate biopsy implementation could be not only plausible, but also mandatory in some subjects with contraindications to MRI or high clinical probability of prostate cancer, associated to negative MRI. Although radio-labelled 11C–choline PET studies have provided equivocal results, because of some overlap with benign prostate hyperplasia and prostatitis (Scher et al, 2007 ), the sensitivity for tumour foci in prostate gland can be high enough to complement MRI findings in the final diagnosis (Hernández-Argüello et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…11 False-positive results remain a chronic problem with choline scans. 12 For instance, a detailed analysis of [ 11 C]choline uptake and prostatectomy histopathology specimens revealed the tracer's inability to distinguish malignant abnormalities from benign prostate conditions including benign prostatic hypertrophy, prostatitis, or prostatic intraepithelial neoplasia. 13 Moreover, the half-life of radioactive carbon is only 20 minutes, mandating that the agent must be made on site at a center with a cyclotron, which is both costly and inaccessible for many patients.…”
Section: Newer Radiotracer That Needs Further Validation In Larger St...mentioning
confidence: 99%
“…The scan was more successful in more advanced cases, including patients with tumors harboring Gleason scores of 8 to 10 with PSA levels of 20 ng/mL or higher; however, MRI also performs well in this group, is usually less expensive, and does not use ionizing radiation . False-positive results remain a chronic problem with choline scans . For instance, a detailed analysis of [ 11 C]choline uptake and prostatectomy histopathology specimens revealed the tracer’s inability to distinguish malignant abnormalities from benign prostate conditions including benign prostatic hypertrophy, prostatitis, or prostatic intraepithelial neoplasia .…”
Section: Diagnosis Of Prostate Cancer With Mri and Petmentioning
confidence: 99%